Aksesibilitas Bagi Wisatawan Penyandang Disabilitas di Museum KAA Bandung - Fitri Fadhilah Sumiarsa; Kiky Yustikasari; Evi Novianti (Peneliti.net, 2022)
Tourism facilities and accessibility need to be reviewed in an effort to realize accessible tourism as a fulfillment of the right of persons with disabilities to travel. The KAA Museum is one of the famous tourist attractions in the city of Bandung. A key objective of this study is to determine what facilities and accessibility tourists with disabilities need. Next, identify the barriers to accessible tourism at the Museum. The research method used is descriptive qualitative with data analysis techniques with field observations and assisted by literature studies. Based on the results, the Museum of the Asian-African Conference fails to meet the criteria as an accessible tourism destination. Lack of government support and licensing are the main obstacles the museum faces.